The Role of Educational Games in Compensating for Educational Losses in Palestine and Syria during Crises - Ali, kareema; Affouneh , Saida; Burgos, Daniel (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to explore the role of educational games in compensating the educational loss in the crises in Palestine and Syria and aims to examine the challenges that face their application and to suggest the best ways to overcome them. Methods: The study relied on conducting semi-structured, open interviews with the study sample, which consisted of twenty people who were intentionally chosen from educators and education experts from Palestine and Syria, and they were asked about the role of educational games in compensating educational losses and increasing students' motivation towards learning in crises. Results: The results showed the role of educational games in increasing students' motivation towards learning, accelerating the learning process, shortening time and effort, and achieving more than one educational goal using one game. Considering the challenges, the economic challenges are represented in low salaries for teachers and poor infrastructure in schools. The technological challenges include teachers’ poor skills in dealing with smart devices and digital educational games. Other challenges are related to the extent of school readiness, the availability of materials and means necessary to employ educational games, and teachers’ knowledge of the types of educational games. Such knowledge includes how to design educational games and adapt them to different school subjects. Other challenges are psychological and social. Conclusions: The study concluded that educational games play an important role in compensating for educational loss and increasing students' motivation towards learning in crises and recommended the need to adopt educational games in the educational process..